Implementasi Bimbingan Konseling dalam Mengatasi Kecemasan Sosial pada Anak Prasekolah: Implementation of Guidance Counseling in Overcoming Social Anxiety in Preschool Children - Fransiska, Fransiska; Adpriyadi, Adpriyadi; Putri, Emiliana Bastiana (Absorbent Mind, 2024)
The experience of entering school for the first time will cause various reactions, one of which is the feeling of anxiety experienced by children when entering a new environment outside their family. To overcome children's anxiety, guidance counseling activities need to be implemented so that children can feel comfortable participating in learning at school The aim of this research is to describe the implementation of guidance counseling in overcoming social anxiety in preschool children. The research method used was qualitative in the form of a case study with a total of 4 sources consisting of the school principal, class teacher, students and parents.The research results show that counseling has a significant role in overcoming the social anxiety of preschool children. The steps for counseling guidance in overcoming social anxiety in preschool children are to be calm, look for the cause of the anxiety experienced by the child and by giving a hug because the anxiety experienced by children is anxiety about being separated from their parents and social anxiety so that the counseling guidance technique used are active, creative and fun.